Tourism studies is a geopolitical instrument: Conferences, Confucius Institutes, and 'the Chinese Dream'. Issue 4 (1st July 2021) - Rowen, Ian
Abstract: Tourism scholarship can advance the multifarious geopolitical projects of state actors and aligned commercial entities. Such effects are achieved not only through tourism itself, but through the production and circulation of politically-inflected forms of knowledge. Such work is conducted by tourism scholars and allied industry and state actors. A first-person account of a 2017 tourism studies conference held at an Australian university demonstrates the argument by examining the ways in which scholars, industry, and state actors navigated and facilitated the geopolitical and geoeconomic agendas of not only domestic but potentially contentious international regimes. The conference received financial and administrative support from state, industry, and academic agencies from both Australia and China. Hosted by the Griffith Institute for Tourism (GIFT) and the Griffith University's Tourism Confucius Institute (TCI), the conference was the third in a series of 'East-West Dialogues on Tourism and the Chinese Dream'. By actively positioning the international collaboration within the rhetorical bounds of the 'Chinese Dream', and by conducting the conference in collaboration with the Tourism Confucius Institute, a quasi-educational operation directly managed by the Chinese party-state, the Australian and international tourism academy implicitly supported the geopolitical designs of the Chinese Communist Party. Renewed attention to academic ethics and increased areal expertise are a necessary response, especially in a time of global geopolitical instability and structural economic transformation in the academy.